2005
DOI: 10.1590/s0102-695x2005000300008
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Davilla elliptica St. Hill (Dilleniaceae)

Abstract: Davilla elliptica St. Hill ("lixinha"), family Dilleniaceae, is commonly used in the Brazilian folk medicine as purgative and stimulant. This work evaluated the antimicrobial activity of the methanol and chloroform extracts of the leaves and barks of D. elliptica using the discdiffusion method. The results obtained showed that the methanolic extracts of the leaves and barks presented antimicrobial activity against the tested microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
2
0
3
Order By: Relevance
“…The anti-Helicobacter pylori activities demonstrated in vitro by minimal inhibitory concentration (MIC) were by Davilla elliptica (EDE) = 250 g/mL and Davilla nitida (EDN) = 125 g/mL. Our results demonstrated that Davilla elliptica and Davilla nitida possessed activity against Helicobacter pylori, properties previously observed against other microorganisms (Michellin et al, 2005). Other studies on plants rich in terpenes, flavonoids and tannins among others, have shown that these compounds could be responsible for the anti-Helicobacter pylori activity (Isobe et al, 2006).…”
Section: Fig 4 Effects Of Davilla Elliptica (Ede) Andsupporting
confidence: 64%
See 1 more Smart Citation
“…The anti-Helicobacter pylori activities demonstrated in vitro by minimal inhibitory concentration (MIC) were by Davilla elliptica (EDE) = 250 g/mL and Davilla nitida (EDN) = 125 g/mL. Our results demonstrated that Davilla elliptica and Davilla nitida possessed activity against Helicobacter pylori, properties previously observed against other microorganisms (Michellin et al, 2005). Other studies on plants rich in terpenes, flavonoids and tannins among others, have shown that these compounds could be responsible for the anti-Helicobacter pylori activity (Isobe et al, 2006).…”
Section: Fig 4 Effects Of Davilla Elliptica (Ede) Andsupporting
confidence: 64%
“…This species also presents potential in the form of immunological and microbiological actions in the tuberculosis control (Lopes et al, 2007). Michellin et al (2005) observed that the methanolic extract of Davilla elliptica possessed antimicrobial activity against different microorganisms, an action probably related to different compounds present in the extract such as tannins, gallic acid, some catechins and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Seus extratos podem modular a ativação dos macrófagos e esse efeito imunoestimulatório pode ser benéfico no aumento da imunidade em doenças infecciosas (CARLOS et al, 2005). A presença de compostos, como taninos, ácido gálico, algumas catequinas e flavonóides nos extratos metanólicos de folhas e das cascas da D. elliptica pode ser responsável pela atividade antimicrobiana dessa espécie (MICHELIN et al, 2005). Em estudo, foi demonstrado que a atividade antimicrobacteriana do extrato de clorofórmio de Davilla elliptica contra Mycobacterium tuberculosis é promissora com concentração inibitória mínima de 62,5 ug.mlˉ¹, mostrando que esta planta pode ter potencial terapêutico no controle imunológico e microbiológica da tuberculose (LOPES et al, 2007).…”
Section: Introductionunclassified
“…É empregada na medicina tradicional como adstringente, tônico, laxativo, diurético (Oliveira & Castro, 1966;Rodrigues & Carvalho, 2001). Estudos realizados com extratos de D. elliptica mostraram efeito imunoestimulatório em ratos, o que sugere um benefício no aumento da imunidade contra doenças infecciosas e propriedades antimicrobianas (Michelin et al, 2005;Carlos et al, 2005). O flavonoide miricetina-3-O-β-galactosídeo isolado do extrato etanólico de folhas apresentou atividade antinociceptiva e antiinflamatória reforçando o uso popular da espécie (Campos, 2006;Azevedo et al, 2007).…”
Section: Introductionunclassified